Design And Development of An Android- Based Book Order System - Ogundokun, Roseline Oluwaseun; Oladele, Rufus O.; Ejegwa, Grace Onyemowo (International Journal of Psychosocial Rehabilitation, 2020)
An ordering system is a collection of elaborate procedures used to handle and manage the ordering process of resources. An online book ordering system is a system which allows customers to purchase books online from a seller’s website. Such customers can search desired books and purchase it online; this study focuses on developing an e-commerce and e-transaction application for an online book sale, providing a catalog-like resource of different books available for purchase. For performance, a shopping cart is usually provided to allow more efficiency. Bookstore management is created to handle queries regarding information on different types of books. An android-based application for ordering books was developed. The system consists of two main subsystems: the administrator system and user system. The system, which was built using a private university in the North Central of Nigeria as a case study, is user-friendly, efficient and robust. The aim of the research is to study the shortcomings in the existing book order systems and provide an effective and efficient book order system for customers and the system will provide an environment where a customer is provided with a secure mode of operation and searching platform to access books online, develop an infrastructure accessible through the internet that can be used to order books and make payment for books bought and lastly the system will create a more user-friendly interface.